Immunohistochemistry combined with NGS to assist the differential diagnosis of multiple primary lung cancer with lymph node metastasis: a case report - Liu, Chang; Zhang, Shuai; Yang, Hong; Bai, Yu; Shen, Yanru; Ren, Yi (Frontiers in Oncology, 2023)
In recent years, the incidence of synchronous multiple primary lung cancers (MPLCs) has gradually increased. Surgery is the preferred treatment for these patients. There are great differences in the driving genes between individual tumors in patients with MPLC, and tumors with targeted mutations do not represent other tumors, which challenges the selection of targeted therapies for patients with MPLC. Driving mutations in each lesion after surgery are crucial for establishing accurate pathological staging and subsequent treatment strategies. There are some mutated genes in the lymph nodes of postoperative metastatic MPLCs, and the tumor cell count/DNA concentration is low, which limits the next-generation sequencing (NGS) detection effect. A combination